B2M is a Biomarker Associated With Immune Infiltration In High Altitude Pulmonary Edema - Yuan, Mu; Hu, Xueting; Xing, Wei; Wu, Xiaofeng; Pu, Chengxiu; Guo, Wei; Zhu, Xiyan; Yao, Mengwei; Ao, Luoquan; Li, Zhan; Xu, Xiang (Combinatorial Chemistry & High Throughput Screening, 2024)
Background: High altitude pulmonary edema (HAPE) is a serious mountain sickness with certain mortality. Its early diagnosis is very important. However, the mechanism of its onset and progression is still controversial. Aim: This study aimed to analyze the HAPE occurrence and development mechanism and search for prospective biomarkers in peripheral blood. Methods: The difference genes (DEGs) of the Control group and the HAPE group were enriched by gene ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis, and then GSEA analysis was performed. After identifying the immune-related hub genes, QPCR was used to verify and analyze the hub gene function and diagnostic value with single-gene GSEA and ROC curves, and the drugs that acted on the hub gene was found in the CTD database. Immune infiltration and its association with the hub genes were analyzed using CIBERSORT. Finally, WGCNA was employed to investigate immune invasion cells' significantly related gene modules, following enrichment analysis of their GO and KEGG. Results: The dataset enrichment analysis, immune invasion analysis and WGCNA analysis showed that the occurrence and early progression of HAPE were unrelated to inflammation. The hub genes associated with immunity obtained with MCODE algorithm of Cytoscape were JAK2 and B2M. RT-qPCR and ROC curves confirmed that the hub gene B2M was a specific biomarker of HAPE and had diagnostic value, and single-gene GSEA analysis confirmed that it participated in MHC I molecule-mediated antigen presentation ability decreased, resulting in reduced immunity. Conclusion: Occurrence and early progression of high altitude pulmonary edema may not be related to inflammation. B2M may be a new clinical potential biomarker for HAPE for early diagnosis and therapeutic evaluation as well as therapeutic targets, and its decrease may be related to reduced immunity due to reduced ability of MCH I to participate in antigen submission.
Keywords: biomarkers